Reconstructing the Connectivity Court System in Indonesia: From Collaborative to Integrative Paradigm - Hakim, Lukman (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study aims to analyze the reconstruction of the criminal justice system from an ad hoc and delegative model to a permanent and attributive model in the Indonesian criminal justice system. This study uses a descriptive-analytical normative juridical method with a legislative, historical, and conceptual approach. Secondary data, including primary, secondary, and tertiary legal materials, were collected through literature studies and analyzed qualitatively using deductive reasoning and various methods of legal interpretation. Departing from the theoretical framework of authority, the rule of law, and equality before the law, this study not only dissects legal dogma but also its implications for civil-military relations and judicial independence. The findings show that connectivity currently functions more as an incidental procedural mechanism that depends on executive discretion, so it is often ignored and opens up room for forum shopping and disparities in punishment between civilian and military perpetrators. On that basis, this study proposes a reconstruction of the connectivity court through the direct attribution of authority in the law to a permanent connectivity court, with a mixed composition of judges and the structuring of the role of the Deputy Attorney General for Military Crimes as dominus litis. This reconstruction is accompanied by recommendations for revisions to the Criminal Procedure Code and the Military Court Law in order to strengthen justice, legal certainty, and judicial independence.